PENGGUNAAN METODE DISCOVERY LEARNING UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS 5 SD NEGERI BORO - Rohadatul Aisy, Rofilah (Program Studi Pendididikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2022)
This study aims to increase the activeness and competence of students in Indonesian class V subjects at SD Negeri Boro through the application of discovery learning methods. This research is a Classroom Action Research (CAR) with the Kemmis and Mc Taggart model which was carried out in two research cycles. The subjects of this study were fifth grade students of SD Negeri Boro for the Academic Year 2021/2022 which opened 25 students. The data collection technique in this study used observation for student learning and activity, tests for cognitive competence, and documentation. The success indicator of this research is more than 70% of student activity and 75% of students reach the KKM of 76. The results show that through the application of the Discovery Learning learning method can increase student activity and competence in Indonesian subjects. This can be seen from: (1) an increase in student activity in each cycle. The activeness of students in the first cycle was 31.29%, and the second cycle was 71.83%; (2) an increase in class average and student learning completeness. The average class in the first cycle is 75.74, and the second cycle is 87.33. Students' learning mastery as measured by cognitive competency tests in the first cycle was 67.74%, and the second cycle was 93.33%.